Belongingness And Love In Jude Deveraux's Moonlight In The Morning Novel (2012): A Humanistic Approach - Citraningtyas, Kurnia; , Dr. Phil. Dewi Candraningrum, M.Ed; , Titis Setyabudi, S.S. M. Hum (2015)
The mayor problem of this study is Jecca Layton who needs love and belongingness from Tristan Aldredge. The objectives of the study are to analyze the novel based on its structural elements and to analyze the novel based on Humanistic Approach. In analyzing Moonlight in the Morning story the researcher uses qualitative method and Humanistic Approach. The object of the study is Jude Deveraux's Moonlight in the Morning, published by Pocket Star Books, 2012. The data sources are primary data and secondary data. The primary data source is the novel Moonlight in the Morning itself and the secondary data sources are the other sources related to the analysis such as the author's biography, the book of fiction, the book of humanistic, dictionary, virtual references, and the other relevant information that support this research. The method of data collection is library research by collecting and recording both of the primary and secondary data. The technique of data analysis used in this study is descriptive qualitative. Based on the analysis above, the researcher draws the following conclusions: first, the researcher concludes that the elements of the novel present a good unity that consists of exposition, complication, climax, and resolution; second, Love and Belongingness of Tristan Aldredge are very needed by Jecca Layton.